Autologous mesenchymal stem cells offer a new paradigm for salivary gland regeneration - Milos Marinkovic; Olivia N. Tran; Hanzhou Wang; Parveez Abdul-Azees; David D. Dean; Xiao-Dong Chen; Chih-Ko Yeh (Nature Publishing Group, 2023)
Abstract Salivary gland (SG) dysfunction, due to radiotherapy, disease, or aging, is a clinical manifestation that has the potential to cause severe oral and/or systemic diseases and compromise quality of life. Currently, the standard-of-care for this condition remains palliative. A variety of approaches have been employed to restore saliva production, but they have largely failed due to damage to both secretory cells and the extracellular matrix (niche). Transplantation of allogeneic cells from healthy donors has been suggested as a potential solution, but no definitive population of SG stem cells, capable of regenerating the gland, has been identified. Alternatively, mesenchymal stem cells (MSCs) are abundant, well characterized, and during SG development/homeostasis engage in signaling crosstalk with the SG epithelium. Further, the trans-differentiation potential of these cells and their ability to regenerate SG tissues have been demonstrated. However, recent findings suggest that the "immuno-privileged" status of allogeneic adult MSCs may not reflect their status post-transplantation. In contrast, autologous MSCs can be recovered from healthy tissues and do not present a challenge to the recipient's immune system. With recent advances in our ability to expand MSCs in vitro on tissue-specific matrices, autologous MSCs may offer a new therapeutic paradigm for restoration of SG function.